SCOPARIA DULCIS: A REVIEW ON ITS PHYTOCHEMICAL AND PHARMACOLOGICAL PROFILE - Paul, Meera (Innoriginal: International Journal of Sciences, 2017)
The aim of the study is to describe importance of Scoparia dulcis and the experimental studies that we have reviewed from different sources. Scoparia dulcis commonly known as ‘sweet broom weed’ is distributed throughout the tropical and subtropical region of the world. The plant is used traditionally as used as a remedy for treating diseases such as; stomach ailments, kidney stones, hypertension, diabetes, inflammation, bronchitis, haemorrhoids, analgesic, antipyretic and urinary disorders. Further, studies reveal the presence of various phytochemical constituents mainly terpenoids, flavonoids and steroids, glycosides and some miscellaneous compounds. These studies reveal that Scoparia dulcis is a source of medicinally active compounds and have various pharmacological effects; hence, this drug encourage finding its new therapeutic uses.